Nucleation and crystal growth : metastability of solutions and melts - Sangwal, Keshra (John Wiley & Sons, Inc., 2018)
A unique text presenting practical information on the topic of nucleation and crystal growth processes from metastable solutions and melts Nucleation and Crystal Growth is a groundbreaking text thatoffers an overview and description of the processes and phenomena associated with metastability of solutions and melts. The author-a noted expert in the field-puts the emphasis on low-temperature solutions that are typically involved in crystallization in a wide range of industries. The text begins with a review of the basic knowledge of solutions and the fundamentals of crystallization processes. The author then explores topics related to the metastable state of solutions and melts from the standpoint of three-dimensional nucleation and crystal growth. Nucleation and Crystal Growth is the first text that contains a unified description and discussion of the many processes and phenomena occurring in the metastable zone of solutions and melts from the consideration of basic concepts of structure of crystallization. This important text: -Outlines an interdisciplinary approach to the topic and offers an essential guide for crystal growth practitioners in materials science, physics, and chemical engineering -Contains a comprehensive content that details the crystallization processes starting from the initial solutions and melts, all the way through nucleation, to the final crystal products -Presents a unique focus and is the first book on understanding, and exploiting, metastability of solutions and melts in crystallization processes Written for specialists and researchers in the fields of materials science, condensed matter physics, and chemical engineering. Nucleation and Crystal Growth is a practical resource filled with hands-on knowledge of nucleation and crystal growth processes from metastable solutions and melts.